Impact of Atrial Fibrillation on Right Ventricular Diastolic Function in Heart Failure with Preserved Ejection Fraction: A Case Report - Harada, Daisuke; Noto, Takahisa; Takagawa, Junya (Archives of Clinical and Medical Case Reports, 2020)
Heart failure with preserved ejection fraction (HFpEF) accounts for almost half of all heart failure cases and its clinical outcomes remain poor due to its heterogeneity. Atrial fibrillation (AF) plays a role in the pathophysiology of HFpEF and rhythm control in AF can improve left ventricular diastolic function; however, the relationship between AF and right ventricular diastolic function has not been fully examined in HFpEF. In this case report, we present a 72-year-old woman who developed HFpEF complicated by AF and less-distensible right ventricle. AF was associated with reversible impairment of RV diastolic function in this case.